Methods of Forecasting Budget Revenues - Kozicki, Bartosz; Waściński, Tadeusz; Lisowska, Agnieszka (Management and Administration Journal, 2020)
In the article the author raises an issue related to the forecasting of budget revenue in Poland after previous analysis primary data on a monthly basis from 2011-2018.. The research data was obtained from the Central Statistical Office. The research was initiated with the analysis and evaluation of data concerning budget revenue in Poland dynamically. Then, on the basis of the results, the prognostic methods were selected. The methods were analyzed and evaluated. The best one was selected and applied in order to conduct the forecasting of the original series. The results obtained in the research were presented in the summary.